Determination of copper Ions (II) in Aqueous Solutions Using Organic Reagent 3-Hydroxy-4-[(2-hydroxy benzylidene) amino] naphthalene Sulphonic Acid-1 (HHBAN) by Spectrophotometric method - Mohammad Maarouf; Ammar Ismaiel (Syrian Journal for Science and Innovation)
Spectrophotometric methods using organic reagents are the most widely used methods because of their rapid, simplicity, low cost, and wide applications. In this research, the possibility of forming a colored complex between copper (II) and the reagent 3-Hydroxy-4-[(2-hydroxy benzylidene) amino] naphthalene Sulphonic Acid-1 to determine copper (II) in aqueous solutions by spectrophotometric method was studied. This research aims to use the reagent to determine copper (II) in aqueous solutions by the Spectrophotometric methodand through the formation of a stable and colored complex, determine the limit of detection, study spectral properties for the complex, and then compare it with other organic reagents. The method focused on the following sections: choosing the optimum pH and temperature, testing some organic solvents and choosing the optimum solvent, determining the molar ratio, the molar absorptivity and stability constant, the optimum concentration of the reagent and the sequence of additions, the liner range, studying the effect of blocked ions, and finally testing the method on lab-prepared samples for copper (II). Practical experiments revealed that the reagent reacts with Copper ions in Britton buffer medium (pH=7) and acetonitrile as a solvent (4%) at room temperature to give an orange complex (λmax=430nm). The composition of complex is [(Cu:L)-(1:2)] and the molar absorptivity and stability constant are calculated and found to be ε=3.236×104l.mol-1.cm-1 and βk =0.5749×103. Calibration is linear over the range (0.3-6) mg/l and the detection limit was 0.02 mg/l. The proposed method was examined on standard solutions of Copper, and RSD% in the range (0.25-5.26)%, and the recovery ( 95-102.5 )%. We conclude from the results that the method is valid and accurate and the proposed reagent can be used to determine copper ions.